Meningkatkan Keterampilan Sosial Pada Muatan PPKn Menggunakan Model Pembelajaran LENTERA Pada Siswa Kelas V - Siti Nur Ainatul Firdausa; Maimunah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this research is that social skills in PPKn content are still low. This research aims to describe social skills. This research uses qualitative research with the PTK type applied in 4 meetings with a total of 23 people in the VB class at SDN Kahakan Kalibaru in the 2023/2024 academic year. Researchers used data collection techniques by observation and learning tests. The results of the research showed that students' social skills at meeting 1 reached 39% with the criteria "quite skilled", increasing at meeting 4 to 78% with the criteria "very skilled". So it can be concluded that the use of the LENTERA model is able to improve students' social skills.